Successful Incorporation of a Plant-Based Menu Into a Large Academic Hospital. Issue 3 (May 2022) - Saldivar, Brittany; Al-Turk, Bashar; Brown, Michelle; Aggarwal, Monica
Unhealthy food choices and poor diet have a significant impact on development and progression of cardiovascular disease. Further, plant-based diets have been shown to mitigate cardiovascular risk factors and improve the health status of patients with cardiovascular disease. Currently, hospitals spend substantial healthcare dollars on food expenditures for inpatient services and recent pushes by the American Heart Association (AHA) and American College of Cardiology (ACC) encourage predominantly or full plant-based diets. The University of Florida has been one of the first institutions to incorporate a fully plant-based menu offering to their inpatient population. Herein, we discuss the program instituted at UF, the challenges faced while making this institutional change, and our solutions to these obstacles. The success of our plant-based initiative can serve as a foundation for other healthcare institutions to incorporate plant-based menu programs.